Evolution of intraocular pressure after cataract surgery in nonglaucomatous patients: A post-hoc analysis of PERCEPOLIS clinical trial data - Jean-Marc Perone; Jean-Charles Vermion; Yinka Zevering; Julie Francois; Alice Nesseler; Grace Gan; Christophe Goetz (PLoS ONE, 2026)
Purpose Intraocular pressure (IOP) drops after cataract surgery, including in nonglaucomatous eyes, but the mechanisms and factors determining this change remain unclear. Thus, post-hoc analysis was conducted on PERCEPOLIS, a large randomized-controlled trial showing non-inferior endothelial-cell loss between two cataract-extraction techniques in nonglaucomatous eyes. Methods Eyes with preoperative and 1-, 3-, and 12-month IOP measurements were identified. None received IOP-lowering medication before or after surgery. To identify possible mechanisms driving postoperative IOP drop, the cohort was categorized according to preoperative IOP (High: 20–29; Intermediate: 15–19; Low: 10–14 mmHg). IOP change in the whole cohort and three subgroups was determined. Multivariable analysis assessed whether age, sex, cataract density, preoperative IOP, anterior-chamber depth, axial length, lens thickness, lens position, relative lens position, cataract-extraction method, effective phaco time, or implant power predicted IOP drop at 3 months in the whole cohort and each subgroup. The literature was reviewed to determine the influence of regression-to-the-mean, a misleading statistical phenomenon, on postoperative IOP drop. Results Whole-cohort IOP dropped from 17.6 ± 3.5 mmHg by 1.9 ± 0.2 (1 month), 2.4 ± 0.2 (3 months), and 1.7 ± 0.2 (12 months) mmHg. IOP drop was greatest in the High subgroup. Preoperative IOP predicted 3-month IOP change in the whole cohort (beta = 0.53 ± 0.04, p < 0.001) and all subgroups (range: beta = 0.36–0.72 ± 0.15–0.30, p = 0.0505–0.001). Male sex also predicted larger whole-cohort IOP drop (beta = 0.79, p = 0.01). Different variables predicted greater IOP change in the three subgroups: male sex in High (beta = 1.63 ± 0.57, p = 0.005), higher implant power in Intermediate (beta = 0.19 ± 0.07, p = 0.01), and hard cataract in Low (beta = 2.14 ± 0.89, p = 0.02). Literature review suggested that regression-to-the-mean accounts for only a small proportion of IOP drop after cataract surgery. Conclusions The IOP drop after cataract surgery may largely be a real biological effect. In normotensive eyes, the strongest predictor of postoperative IOP drop was preoperative IOP. Distinct mechanisms may mediate the IOP change in normotensive eyes.